PENGGUNAAN METODE PICTURE AND PICTURE UNTUK MENINGKATKAN MINAT BELAJAR ILMU PENGETAHUAN SOSIAL SISWA KELAS IV SDN 022 SINTONG KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Yasi '; Sri Kartikowati; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: Picture and Picture learning method is a series of teaching materials delivered by showing pictures - concrete images that the students can understand clearly about the true meaning of the teaching materials presented to him. Thus, the main ingredient of the use of methods of picture and Picture is a picture - a picture that involves learning materials. The purpose of this study is to investigate the use of picture and Picture In the method of increasing student interest in learning social studies grade IV SDN 022 Sintong Tanah Putih Rokan Hilir. Where the research was conducted in SDN 002 Sintong Tanah Putuh. The sample used is siwi fourth grade students numbered 21 people, consisting of 9 men and 12 women. Data was collected using observation sheet for teachers, students and student interest. Analysis technique used is sheet activities of teachers, the observation sheet and interest in learning. From the results of data analysis that has been done shows a method of picture and picture can improve the learning interest of fourth grade students of SDN 022 Sintong Tanah Putih Rokan Hilir proven and is one of the exciting learning methods in the learning process in the classroom can be accepted. From these results it is suggested that the application of methods Picture and Picture can be used as a method of learning that can improve the quality of teachers and the quality of students in the school.Keywords: Picture and Picture Method , learning to interst